Selected problems of fractional systems theory - Kaczorek, T. (Tadeusz) 1932-; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
This monograph covers some selected problems of positive fractional 1D and 2D linear systems. It is an extended and modified English version of its preceding Polish edition published by Technical University of Bialystok in 2009. This book is based on the lectures delivered by the author to the Ph.D. students of the Faculty of Electrical Engineering of Bialystok University of Technology and of Warsaw University of Technology and on invited lectures in several foreign universities in the last three years.
Fractional discrete-time linear systems -- Fractional continuous-time linear systems -- Fractional positive 2D linear systems -- Pointwise completeness and pointwise degeneracy of linear systems -- Pointwise completeness and pointwise degeneracy of linear systems with state-feedbacks -- Realization Problem for positive fractional and continuous-discrete 2D linear systems -- Cone discrete-time and continuous-time linear systems -- Stability of positive fractional 1D and 2D linear systems -- Stability analysis of fractional linear systems in frequency domain -- Stabilization of positive and fractional linear systems -- Singular fractional linear systems -- Positive continuous-discrete linear systems -- Laplace transforms of continuous-time functions and z-transforms of discrete-time functions.
Electronic reproduction.
Keywords: Fractional calculus; Electronic books